1999
DOI: 10.1016/s0002-9270(98)00747-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender, age, and body weight are the major predictive factors for bone mineral density in Crohn's disease: a case-control cross-sectional study of 113 patients

Abstract: Gender, age, and body weight are the major determinants of bone mineral density in patients with Crohn's disease. As in healthy individuals, the combined effect of these factors account for up to 50% of the variability in bone mineral density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
1
4

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 0 publications
9
41
1
4
Order By: Relevance
“…In contrast, a study of patients in Italy [26] does not mention a relationship of age to BMD, but found the femur T-score to be significantly inversely related to disease duration. No predictive value for BMD was ascribed to disease duration by the Danish [23] and Canadian [25] groups mentioned above. The latter group adjusted disease duration for age.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, a study of patients in Italy [26] does not mention a relationship of age to BMD, but found the femur T-score to be significantly inversely related to disease duration. No predictive value for BMD was ascribed to disease duration by the Danish [23] and Canadian [25] groups mentioned above. The latter group adjusted disease duration for age.…”
Section: Discussionmentioning
confidence: 83%
“…However, in Canada relapses of Crohn disease peaked in autumn and winter, with a summer trough [22]. Researchers in Denmark [23], southern Norway [24] and Toronto, Canada [25] have recently reported a negative association of bone mineral density with age, at least in some locations of DEXA measurements. This is in partial agreement with the nonsignificant decrease of T-score with age in patients with active disease in our study, but not quite with the borderline significant increase of T-score in patients with inactive disease up to age 35 followed by its borderline significant decrease thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is some information supporting the relationship between steroid use and osteoporosis [6], the data regarding the translation of this into elevated fracture risk in the IBD population are unclear, as are data regarding the influence of disease duration or extent. Card et al found a significant association between corticosteroid use and fractures in IBD patients [13,28], but other studies failed to support this association [14,15,18,29] and found equal prevalence and cumulative dose of steroid use between IBD patients who developed fractures and controls. Similarly, disease duration or extent have not been consistently associated with fractures in IBD patients as a whole, but may play a role in select subgroups [7,18].…”
Section: Discussionmentioning
confidence: 99%
“…Card et al found a significant association between corticosteroid use and fractures in IBD patients [13,28], but other studies failed to support this association [14,15,18,29] and found equal prevalence and cumulative dose of steroid use between IBD patients who developed fractures and controls. Similarly, disease duration or extent have not been consistently associated with fractures in IBD patients as a whole, but may play a role in select subgroups [7,18]. Another limitation of our study includes restriction of our analysis to patients and controls with fractures requiring hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation